Geological and Geotechnical State of the Nisane Khola Landslide, Dharan, Sunsari, Nepal: a case study - Adhikari, Drona; Silwal, Champak Babu; Giri, Suraj (Himalayan Journal of Science and Technology, 2020)
Geological and landslide mapping was carried out in order to delineate the geological and geotechnical state of the Nisane landslide, situated in Dharan Sub-Metropolitan City, Sunsari, Nepal, which has been obstructing the Koshi Highway time and again. The affected area bears metasedimentary and sedimentary rock sequences of the Lesser Himalaya and the Siwalik, respectively. The Dharapani Thrust separates the Chiuribas Formation and the Tamrang Formation of the Lesser Himalaya whereas the Main Boundary Thrust separates the Tamrang Formation and the Siwalik. The Nisane landslide is an old landslide situated in the structurally weak zone having variable activation period. Recently, the landslide reactivated as intense slide after the Gorkha Earthquake, 2015 and is occasionally obstructing the Koshi Highway. The subsidence in highway indicates the landmass is creeping along the tension crack. Kinematic analysis, Rock Mass Rating (RMR) and Slope Mass Rating (SMR), based on the field observation, measurement and laboratory testing, was carried out in eight different slopes of the slide. The results suggested majority of slopes suffers the wedge and plain failures along the major joint sets. The rock masses are of fair class and the slopes are unstable to partially stable. The slopes of major slide are vulnerable and seeks for immediate sustainable treatment.